A-CAT'S health: operational parameters. Issue 1 (29th April 2016) - Sharma, Jitendra
Abstract : Subject area: Operations management. Study level/applicability: This case can be used in a core course in production and operation management; process management and courses like design and planning of operations at the graduate level, preferably during or after the basic operations module of the course. The case focuses on the use of a process analysis that decomposes the problem into a number of easily solvable sub-problems, each of which could be distinctly analyzed and solved. The case can also be effectively utilized in elective courses on process reengineering, concurrent engineering/management, process management, capacity planning, etc. Ideally, this case can be discussed for 75 to 90 minutes. Case overview: The case describes the situation facing the operations supervisor, Sunil Mehta, of A-CAT Corp. in Vidarbha Region, Maharashtra, India. A-CAT Corp. was a mid-sized manufacturer and distributor of domestic electrical appliances, largely catering to the price-sensitive rural population. The firm operated two medium-sized facilities in one of the remote districts in Vidarbha, and these manufacturing units had been in operation since 1986. A-CAT manufactured a relatively wide range of electrical appliances for household use. Typical products from its stable included TV signal boosters, transformers, FM radio kits, electronic ballasts, battery chargers, voltage regulators, etc. The voltage regulators manufactured by A-CAT were used for many different purposes, although the focus was on its flagship product, VR500. The issue at hand for Sunil Mehta, operations supervisor at A-CAT, was to get data and act right; more often than not, this boiled down to critical information which everyone in the firm kept collecting but were too busy to use and utilize. The challenge was to select the right kind of data needed from the data-deluge that the company had in their databases. The eluding objective was to use it for the betterment of the firm. The challenge was to utilize the data that the workers and other operators kept logging in and, in the process of doing so, came up with some solutions to the problems faced on the operational front. Expected learning outcomes: The case teaching and learning objectives are as following: to grasp the basics of process and process parameters; to understand the interrelationship between capacity, utilization, efficiency and productivity of a process; and to carry out process capacity analysis in assessing the performance of the firm on different metric drivers. The case also provides a very good foundation for understanding process parameters in a simple and lucid manner. To make right computations and not to use the terms and terminology in "cook book" or "strait jacketed" manner, students need to realize the parameters and their understanding changes from situation to situation. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 9: Operations and Logistics.